2004
DOI: 10.1081/imm-200038753
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Analysis of Immunorestoration and Recovery with Conventional and Immunotherapeutic Protocols in Canine Generalized Demodicosis: A Newer Insight of Immunotherapeutic Efficacy of T11TS

Abstract: Demodex canis is a natural inhabiting mite of canine skin. Immunological disorder or genetic disorder induces the Demodex population to proliferate vigorously resulting in generalized demodicosis with consequent chronic immunosuppression. Signs of generalized demodicosis include alopecia, crysting, erythema, secondary pyoderma etc. Amitraz, an acaricide, is used conventionally for the treatment of generalized demodicosis. In many instances, the disease relapses due to the residual immunosuppression. The need o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 27 publications
(26 reference statements)
0
7
0
Order By: Relevance
“…The underlying reasons for the generalized manifestation of demodectic mange in deer are unknown but could reflect host immunologic or genetic factors or concurrent endocrine disorders, as has been suggested in domestic canids (Canis familiaris). 17,21,22 The effects of demodectic mange on the host are usually subclinical, and most white-tailed deer in the present study were in good nutritional condition and exhibited normal behavior. However, clinical disease in the host can result from parasite expansion, which is thought to be secondary to immunosuppression from transient or prolonged stress, poor nutrition, or concurrent infections.…”
Section: Discussionmentioning
confidence: 97%
“…The underlying reasons for the generalized manifestation of demodectic mange in deer are unknown but could reflect host immunologic or genetic factors or concurrent endocrine disorders, as has been suggested in domestic canids (Canis familiaris). 17,21,22 The effects of demodectic mange on the host are usually subclinical, and most white-tailed deer in the present study were in good nutritional condition and exhibited normal behavior. However, clinical disease in the host can result from parasite expansion, which is thought to be secondary to immunosuppression from transient or prolonged stress, poor nutrition, or concurrent infections.…”
Section: Discussionmentioning
confidence: 97%
“…The demodex infestation itself has subsequently been shown to cause further immunosuppression in these patients. While human patients undergoing chemotherapy have been shown to have an increased incidence of demodex infestation it appears as though we may have identified a highly susceptible population pre‐chemotherapy treatment. The immune dysregulation that occurs associated with the development of indolent lymphoma may specifically make these patients more prone to developing such an infestation.…”
Section: Discussionmentioning
confidence: 99%
“…Generalized demodicosis is a complex disease whose exact pathogenesis remains unclear. It is believed that both genetic and immunologic factors play important roles in its development and progression 1–5 . It has been suggested that juvenile‐onset demodicosis results from an inherited autosomal recessive gene that expresses a demodex‐specific T‐cell deficiency 4 while the adult‐onset form is associated with generalized immunosuppression elicited by underlying disease 1,2 …”
Section: Introductionmentioning
confidence: 99%